PERAN GURU KELAS DALAM IMPLEMENTASI LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH DASAR - Nampi Irayani Blorton; Paulina Arokoil, Paulina Lambila, Yessy Mata, Petrus Mau Tellu Dony, Yermia S. Wabang (JIP: Jurnal Ilmu Pendidikan, 2025)
This study aims to examine the strategic role of classroom teachers in implementing guidance and counseling (GC) services in elementary schools, considering the limited availability of professional school counselors at the primary level. Classroom teachers have a dual role: as educators and as mentors who assist students in dealing with academic, social, and emotional challenges. This research uses a descriptive qualitative approach through observations and interviews with classroom teachers, principals, and students to understand how GC services are practiced directly within the school environment. The findings show that classroom teachers actively carry out various types of GC services, such as orientation, information dissemination, individual counseling, and communication with students’ parents. However, most of these practices are still conducted informally and intuitively, lacking professional guidance or a systematic approach. Limited training, time constraints, and heavy workloads are the main obstacles to the optimal implementation of GC services. Despite these challenges, some teachers demonstrate initiative by using creative and adaptive approaches, such as storytelling, educational games, and routine psychological monitoring of students. Classroom teachers are considered to have great potential in building empathetic and meaningful relationships with students due to the high frequency of daily interaction. This reinforces their role as key facilitators in supporting the development of students' character and personality. Therefore, policies and training programs are needed to enhance the capacity of classroom teachers to carry out guidance functions professionally. In addition, synergy among schools, governments, and parents is essential to create an educational ecosystem that supports GC services as an integral part of basic education. With such support, classroom teachers can more effectively contribute to shaping students who are not only intellectually intelligent but also socially and emotionally mature.